Northrop Frye : eastern and western perspectives - O'Grady, Jean, 1943-; Wang, Ning, 1975- (Frye studies., 2003)
Drawn from papers given at an international symposium on Northrop Frye in Hoh-Hot, Inner Mongolia, this volume offers insights intoFrye's theoretical approaches and the new context provided by cross-cultural questions.